Electron transport estimated from electron spectra using electron spectrometer in LFEX laser target experiments. (May 2016) - Ozaki, T; Hata, M; Matsuo, K; Kojima, S; Arikawa, Y; Fujioka, S; Sakagami, H; Sunahara, A; Nagatomo, H; Johzaki, T; Yogo, A; Morace, A; et al.
Abstract: Hot electrons which are generated from targets irradiated by a high-intense laser are measured by two electron spectrometers (ESMs). However, total electron energy observed by the ESM is only less than 1%. Hot electrons are confined by self-fields due to the huge current. When an external magnetic field of several hundred Tesla is applied during the laser irradiation on targets, the ESM signals always increase. In the simulation, the same result can be obtained. The reason is that the Alfvén limit can be mitigated due to the external longitudinal magnetic field.